2021
DOI: 10.1097/olq.0000000000001384
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Preexposure Prophylaxis Knowledge, Attitudes and Perceptions of Sexual Health Risk in an Age of Sexually Transmitted Infection Antimicrobial Resistance

Abstract: A mixed methods study of cisgender men/transpersons who have sex with men sexual health clinic attendees found that preexposure prophylaxis reduced anxiety and may increase likelihood of condomless anal intercourse, but risk of sexually transmitted infection antimicrobial resistance was not seen as an immediate threat. Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Our qualitative study indicates that MSM may have a good understanding of PrEP and why it is of use in key populations such as MSM. For our participants, PrEP was valued for its impact on reducing HIV as well as reducing anxiety over HIV acquisition; a finding found in several previous studies [19][20][21]. In our study, MSM also had a reasonable knowledge of many STIs, with HIV, gonorrhoea and chlamydia being most familiar to participants.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our qualitative study indicates that MSM may have a good understanding of PrEP and why it is of use in key populations such as MSM. For our participants, PrEP was valued for its impact on reducing HIV as well as reducing anxiety over HIV acquisition; a finding found in several previous studies [19][20][21]. In our study, MSM also had a reasonable knowledge of many STIs, with HIV, gonorrhoea and chlamydia being most familiar to participants.…”
Section: Discussionsupporting
confidence: 60%
“…While some participants were aware of AMR STIs, this was not viewed as a current and immediate risk but felt that resistant STIs would need to be more prevalent and untreatable before they would consider changing their behaviour. The belief that AMR STIs were not a personal risk was also identified in qualitative work conducted in Bristol among PrEP users [ 19 ]. This suggests that the problem of STI AMR would need to become a personal, direct, and serious threat before condoms are used alongside PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of PrEP awareness was the second most frequently reported barrier, tied with lack of PrEP willingness and lack of access to a PrEP provider ( n = 16) [25, 27, 29–35, 37, 44, 56, 57, 59, 61, 63]. Although awareness was high among MSM (81%–100%) [25, 27, 33, 35, 37, 44, 56, 57], it was much lower among ethnic minorities (13%–54%) [29, 30, 34, 56, 57] and trans‐identifying people (16%–66%) [61] [56].…”
Section: Resultsmentioning
confidence: 99%
“…Lack of PrEP knowledge was the most studied barrier (Figure 3): it was investigated in 19 of the studies [10, 24, 25, 27, 33–35, 41, 44, 46, 48, 51, 53, 56, 58, 59, 61, 62, 65]. One study found that 44% of survey respondents listed lack of PrEP knowledge as a direct barrier to PrEP use [56].…”
Section: Resultsmentioning
confidence: 99%
“…Current qualitative studies have found that the risk of STI AMR is not perceived as an immediate threat by certain MSM. 26 However, we do not yet know to what extent this is attributable to all MSM and whether targeted awareness campaigns may change such perceptions. Nevertheless, the high prevalence of combined resistance to fluoroquinolones and macrolides in those with recurrent STIs suggests that a period of untreatable STIs is at hand.…”
Section: Discussionmentioning
confidence: 98%